(untitled) (Al-Academy, 2019)
The study dealt with the design of tourist resting units in the Iraqi Marshes in contemporary design methods while preserving the heritage. The first chapter contained the research problem which is the important event of the inclusion of the Marshes in the World Heritage List. This research is important because it aims to develop the tourist reality of the Marshlands. The second chapter dealt with three sections the first of which is tourism in the marsh environment, the second one dealt with the structure of tourist space and the third dealt with the design methods of the tourist resting units in the Iraqi marshes. The most important results of the research are the following: the sample models have taken design methods that reflect the cultural heritage of the communities of these models. Some models have achieved harmony between the style of the designer and the taste and desire of the tourist, while other models have not